2019
DOI: 10.19102/icrm.2019.101006
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Regulation of Voltage-gated Calcium Channels in Arrhythmias

Abstract: Calcium flowing through voltage-dependent calcium channels into cardiomyocytes mediates excitation-contraction coupling, controls action-potential duration and automaticity in nodal cells, and regulates gene expression. Proper surface targeting and basal and hormonal regulation of calcium channels are vital for normal cardiac physiology. In this review, we discuss the roles of voltage-gated calcium channels in the heart and the mechanisms by which these channels are regulated by physiological signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…So far, more limited studies have been performed on modeling the gastrointestinal tract than the heart. While different models have been suggested for the heart, including electrophysiological, electrochemical, three-dimensional, FEM, and quantitative (13,27,28). Finally, considering the results of this study, pacemakers may be designed to control the contractile activity of the gastric smooth muscle, such as the heart (7,29).…”
Section: Discussionmentioning
confidence: 88%
“…So far, more limited studies have been performed on modeling the gastrointestinal tract than the heart. While different models have been suggested for the heart, including electrophysiological, electrochemical, three-dimensional, FEM, and quantitative (13,27,28). Finally, considering the results of this study, pacemakers may be designed to control the contractile activity of the gastric smooth muscle, such as the heart (7,29).…”
Section: Discussionmentioning
confidence: 88%
“…Voltage-dependent calcium channel subunit alpha2delta2 (CACNA2D) is known to be responsible for regulating calcium transportation and signal responses in cardiomyocytes [ 96 ], and it has been reported that miR-1231 aggravates arrhythmia by targeting CACNA2D2 [ 97 ]. Considering that the dysfunction of calcium channels has been closely associated with cardiac hypertrophy, arrhythmias, or even heart failure [ 98 ], it is likely that the increase in miR-1231 in EAT imposes potential harm to the heart.…”
Section: Micrornas Expressed In Human Eatmentioning
confidence: 99%
“…Depending on the pharmacological sensitivity and activation rate, so far, six types of calcium channels have been observed. These include T, L, N, P, Q, and R types [ 23 ], which are named according to their responses to the voltage applied. The most significant calcium channel subtypes are L-type and T-type, which play key roles in regulating heart functions.…”
Section: Calcium Channelsmentioning
confidence: 99%
“…Both L-type and T-type are voltage-gated. L-type channels are long-lasting and their activation requires resilient depolarization, whereas T-type channels are transient [ 23 ]. A comprehensive understanding of the structural properties of these channels opens a wider pathway through which to identify their importance in cardiovascular pathologies.…”
Section: Calcium Channelsmentioning
confidence: 99%
See 1 more Smart Citation